Scaling Up the Family Integrated Care Model in a Level IIIC Neonatal Intensive Care Unit: A Systematic Approach to the Methods and Effort Taken for Implementation - Moreno-Sanz, Bárbara; Montes, María Teresa; Antón, Marta; Serrada, María Teresa; Cabrera, Marta; Pellicer, Adelina (Frontiers in Pediatrics, 2021)
Background: Family Integrated Care (FICare) integrates parents in the direct care of their child while the healthcare personnel act as teacher and guide. Up to date, most reports on the feasibility of this model refer to stable preterm infants admitted to Neonatal Intensive Care Units(NICU). Objectives: To scale up and adapt FICare to make it suitable in a level IIIC NICU, that cares for extreme prematurity and other complex medical or surgical neonatal conditions. Material and methods: Step 1-Creation of the FICare implementation team (FICare-IT) and baseline analysis of current procedures for critical care to identify needs, wishes and requirements; protocol elaboration tailored to our cultural, architectural, and clinical context (March 2017-April 2018). Step 2-Dissemination strategy by FICare-IT acting as primary trainers and mentors to ensure the education of 90% of nursing staff (May 2018-July 2018). Step 3-Piloting and evaluation for procedures’ refinement (July 2018-December 2020). Results: A rigorous but flexible protocol was edited. The FICare educational manual included two curricula: for healthcare professionals/staff (Training the trainers) and for families (Education of caregivers), the latter being categorized in two intervention levels (basic and advanced), depending on the infant care needs and parent’s decision. Seventy six families and 91 infants (74.7% preterm; 18.7% complex surgery; 6.6% others) were enrolled in the pilot. No differences in acceptance rate (overall 86.4%), or in the number of infant-family dyads in the program per month were observed, considering the pre- and post-Covid-19 pandemic periods. All families, except for one who dropped out of the program, completed the agreed individualized training. Mothers spent more time in NICU than fathers (p<0.05); uninterrupted time spent by mothers in NICU was longer during the pre-pandemic period (p<0.01). Observed time to reach proficiency by task was within the expected time in 70% of the program contents. The parents revealed educational manual, workshops and cot-side teaching sessions as essential for their training, and 100% would accept to enter the FICare program again. Conclusions: The principles of FICare model are suitable in all levels of care in NICU. Leadership and continuous evaluation/refinement of implementation procedures are essential components to achieve the objectives.